A Practical Approach to Teaching Differential Robot Control Using a Goal-to-Goal Interface - Amorim, Johann S. J. C. C.; Moraes, Camile A.; S. Neto, Accacio F. dos; Amorim, Josef G. J. C. C.; Santos, Patricia S.; Lima, José; Haddad, Diego; Pinto, Milena F. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2024: Anais do XVI Simpósio Brasileiro de Robótica e XV Workshop de Robótica na Educação, 2024)
This paper presents an interface to assist students in performing robot controllers. This application is designed to stabilize the movement of a goal-to-goal robot. The primary objective is to enhance the learning experience by offering an easy application that showcases the robot's behavior based on its kinematic model. The paper outlines the various stages involved in developing and testing this simple interface, including a study of the kinematics of differential robots. It discusses the discrete-time equations for goal-to-goal behavior, the data required to obtain the controller, the application of the controller in a discrete microcontroller, and the development of code to simulate the robot's behavior. The results show the developed interface and the possible outcomes through the use of this application in control classes.